2016
DOI: 10.1364/oe.24.005323
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing dynamic laser speckle to probe nanoscale morphology evolution in nanoporous gold thin films

Abstract: This paper demonstrates the use of dynamic laser speckle autocorrelation spectroscopy in conjunction with the photothermal treatment of nanoporous gold (np-Au) thin films to probe nanoscale morphology changes during the photothermal treatment. Utilizing this spectroscopy method, backscattered speckle from the incident laser is tracked during photothermal treatment and both the characteristic feature size and annealing time of the film are determined. These results demonstrate that this method can successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Autocorrelation can be used to characterize the temporal evolution of the Urea/Diatom dynamic surface under analysis Rabal and Braga (2008); Chapman et al (2016); Mendoza-Herrera et al (2021). Autocorrelation function of the pattern is defined by Chapman et al (2016):…”
Section: Autocorrelationmentioning
confidence: 99%
See 1 more Smart Citation
“…Autocorrelation can be used to characterize the temporal evolution of the Urea/Diatom dynamic surface under analysis Rabal and Braga (2008); Chapman et al (2016); Mendoza-Herrera et al (2021). Autocorrelation function of the pattern is defined by Chapman et al (2016):…”
Section: Autocorrelationmentioning
confidence: 99%
“…Qualitative methods allow segmentation of the image according to its speckle activity, such as generalized differences Arizaga et al (2002), LASCA Arizaga et al (2006), Fujii Fujii et al (1987); Ansari and Nirala (2015); Minz and Nirala (2014); Sauude et al ( 2012) and temporal differences Ansari and Mujeeb (2018) methods, among others Rabal and Braga (2008). Quantitative measurements of the speckle activity are based on the autocorrelation Chapman et al (2016), the moment of inertia of the co-occurrence matrix (COM) Arizaga et al (1999) and the statistical cumulants Pajuelo et al (2003), the temporal evolution of the speckle pattern texture Arizaga et al (1999); DaryMojica-Sepulveda et al (2018), empirical decomposition Federico andKaufmann (2006), spatio-temporal correlation Zdunek et al (2007). The dynamic speckle technique enables the determination of sample characteristics across multiple applications.…”
Section: Introductionmentioning
confidence: 99%
“…Ex situ characterization methods, as well as a wide range of in situ spectral techniques, have been employed to study the dynamic evolution of Au NPs. , The in situ liquid cell scanning transmission electron microscopy (S/TEM) technique allows for the direct observation of dynamic processes in a liquid layer, such as the nucleation and growth of NPs from liquid phase precursor solutions, toward elucidating growth mechanisms, crystallization processes, and self-assembly. Many unexpected mechanisms of colloidal nanocrystal growth and morphological evolution have been reported . For example, by imaging through thin droplets (∼30 nm) of an aqueous solution inside a liquid cell, Loh et al reported each step in the growth of gold and Ag NPs in water, from the initial supersaturated homogeneous solution, spinodal decomposition, solidification, and crystallization, resulting in Ag NPs ranging between 10 and 38 Å in size.…”
Section: Introductionmentioning
confidence: 99%
“…Ex situ characterization methods, as well as a wide range of in situ spectral techniques, have been employed to study the dynamic evolution of Au NPs. 21,22 The in situ liquid cell scanning transmission electron microscopy (S/TEM) technique 23 a liquid layer, such as the nucleation and growth of NPs from liquid phase precursor solutions, 24 toward elucidating growth mechanisms, crystallization processes, and self-assembly. 25−30 Many unexpected mechanisms of colloidal nanocrystal growth and morphological evolution have been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, there is little control over the free corrosion process during dealloying. The desire to utilize NPG in various applications as well as fundamental studies motivates the development of novel fabrication and synthesis techniques since NPG properties are modified by morphological controls of the porous structures [5,6].…”
Section: Introductionmentioning
confidence: 99%